2020
DOI: 10.1016/j.jhazmat.2019.121673
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash and zinc slag blended geopolymer: Immobilization of hazardous materials and development of paving blocks

Abstract: The potential for practical application of fly ash, zinc slag and their blends for geopolymer synthesis at ambient temperature have been investigated in this paper. Fly ash is an alumino-silicate byproduct suitable for geopolymer reaction, but its low reactivity at ambient condition is the restriction of its bulk utilization. Above limitation can be overcome by blending with zinc slag (ZS). Additionally, ZS contains heavy and toxic metals (Pb, Zn, Cr, Cd, As), which can be stabilize in Al-Si based geopolymer n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Various papers have included blast furnace slag as a precursor for producing geopolymers containing quarry waste [29,33,34,36,37,43,[53][54][55][56][57][58][59]. The potential of using geopolymers consisting of copper mine tailings and slag for pavement construction was investigated [33].…”
Section: Ground Granulated Blast Furnace Slagmentioning
confidence: 99%
“…Various papers have included blast furnace slag as a precursor for producing geopolymers containing quarry waste [29,33,34,36,37,43,[53][54][55][56][57][58][59]. The potential of using geopolymers consisting of copper mine tailings and slag for pavement construction was investigated [33].…”
Section: Ground Granulated Blast Furnace Slagmentioning
confidence: 99%
“…Kaur et al [21] indicated that approximately 1.2 times more compressive strength could be obtained when a combination of NaOH and Na 2 SiO 3 was added to fly ash, compared to the use of NaOH only. The compressive strength increased as NaOH concentration increased from 8 to 16 M. Thus, the increase of NaOH concentration caused a significant acceleration of dissolution reactions, promoting the early stages of the geopolymerization process [24,25]. A maximum compressive strength of 40.42 MPa was obtained when fly ash was activated with 16 M NaOH and mixed with a sand to fly ash ratio of 3:1 [21].…”
Section: Introductionmentioning
confidence: 97%
“…The curing temperature and aging period not only play a significant role as accelerators of the chemical reactions, but also determine the extent of those reactions [30,36]. The aging periods mostly used to test the compressive strengths of geopolymer materials are 7 and 28 days [21,25,[37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations